Tourism Practices in the Inland Areas of the Abruzzo Apennines. The Challenges of the Tourism Promotion and Enhancement Strategy of the Terre della Baronia District - Chiarella, Stefania; Magnani, Elisa (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2024)
The paper explores the tourist promotion strategies of a territory in the Abruzzo Apennines using the lens of proximity tourism, in order to reflect whether the increase in the tourist flow in the area recorded in the last two years can trigger virtuous mechanisms aimed at a better tourist management. The first section proposes a theoretical reflection on proximity tourism while the second problematizes the nature of the inner areas of the Abruzzo region and the potential for its territorial development in terms of tourism, with a specific focus on the Terre della Baronia District, a territory that is part of the Gran Sasso and Monti della Laga National Park which experienced a real explosion of domestic tourism in the years 2020 and 2021, following the reduced international mobility induced by Covid-19.